Independent measurement of the Hoyle state β feeding from B 12 using Gammasphere - Munch, M. (2016)
Using an array of high-purity Compton-suppressed germanium detectors, we performed an independent measurement of the β-decay branching ratio from 12B to the second-excited state, also known as the Hoyle state, in 12C. Our result is 0.64(11)%, which is a factor ∼2 smaller than the previously established literature value, but is in agreement with another recent measurement. This could indicate that the Hoyle state is more clustered than previously believed. The angular correlation of the Hoyle state γ cascade has also been measured for the first time. It is consistent with theoretical predictions.